2009
DOI: 10.1120/jacmp.v10i3.2896
|View full text |Cite
|
Sign up to set email alerts
|

Time delays and margins in gated radiotherapy

Abstract: In gated radiotherapy, the accuracy of treatment delivery is determined by the accuracy with which both the imaging and treatment beams are gated. Time delays are of four types: (1) beam on imaging time delay is the time between the target entering the gated region and the first gated image acquisition; (2) beam off imaging time delay is the time between the target exiting a gated region and the last image acquisition; (3) beam on treatment time delay is the time between the target entering the gated region an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 24 publications
3
47
0
2
Order By: Relevance
“…1 Following this recommendation, several groups have determined time delays on a variety of gating systems. [2][3][4][5][6][7] Jin and Yin found a 170 ms time delay in ExacTrac-gated EPID imaging on a Novalis system (BrainLab, Heimstetten, Germany) using a regular, sinuosidal-like motion phantom. 2 Tenn et al used regular motion with a small amount of hysteresis and found a latency of 60 ± 20 ms. 4 Smith et al found mean time delays between transponder positions and linac modulation were 75 ± 13 ms (beam-on) and 65 ± 12 ms (beam-off) for Calypso Medical 4D electromagnetic tracking system (Seattle, WA) with a Varian Trilogy linac using a circular motion phantom and a single patient trajectory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Following this recommendation, several groups have determined time delays on a variety of gating systems. [2][3][4][5][6][7] Jin and Yin found a 170 ms time delay in ExacTrac-gated EPID imaging on a Novalis system (BrainLab, Heimstetten, Germany) using a regular, sinuosidal-like motion phantom. 2 Tenn et al used regular motion with a small amount of hysteresis and found a latency of 60 ± 20 ms. 4 Smith et al found mean time delays between transponder positions and linac modulation were 75 ± 13 ms (beam-on) and 65 ± 12 ms (beam-off) for Calypso Medical 4D electromagnetic tracking system (Seattle, WA) with a Varian Trilogy linac using a circular motion phantom and a single patient trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…These time delays were measured on a variety of Varian linacs using the Real-time Position Management (RPM) system (Varian Medical Systems, Palo Alto, CA) and an overall temporal misalignment of the imaging and treatment systems of 200 ms was found. 5 Guana found an overall time delay of 750 ms in a prospectively gated axial 4DCT on a AcQSim CT simulator (Philips Medical Systems, Cleveland, OH) using RPM. 6 Goharian and Khan found an overall time delay of 346 ms for a Philips Brilliance BigBore TM (Philips Medical Systems, Madison, WI) scanner with the RPM.…”
Section: Introductionmentioning
confidence: 99%
“…This paper describes a sequence of carbon-ion treatment planning for respiratory-gated therapy to improve the dose coverage to a target and the dose suppression in surrounding normal tissues through appropriate margin setting and range compensator design. Some papers have reported on the delays of gating systems [1012] and treatment planning strategies of particle beam therapy for mobile tumors [13, 14]. However, for respiratory gating, papers compiling the practical processes such as proposing the method for deriving appropriate timings of image acquisitions including delay times of the gating systems, subsequent margin setting and range compensator design in treatment planning, its clinical application, and verification of the planned margins with clinical experience have not been reported so far, especially for ion beam therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A time delay in a respiratory gating system could cause unexpected phase mismatch for respiratory-gated RT; thus, geometric and dosimetric errors might occur [19] [20]. However, the time delay between recognition of the marker position and the start or stop of dose delivery was 0.03 s for respiratory-gated RT using the RTRT system [21].…”
Section: Discussionmentioning
confidence: 99%